Lymphocyte-monocyte ratio as predictive factors for huvos scores in osteosarcoma extremities treated by neoadjuvan chemotherapy (cisplatin and doxorubicin) - Tusan Sidharta, I. Made; Kawiyana, I. Ketut Siki; Suyasa, I. Ketut (International Journal of Research in Medical Sciences, 2020)
Background: Chemotherapy is a vital treatment in osteosarcoma but it’s responses are difficult to predict, and there are still no biomarkers that can estimate the prognosis of chemotherapy. Lymphocytes and monocytes are key immune cells which are examined on complete blood count test before chemotherapy and often associated with prognosis of various malignancies. Low lymphocyte-monocyte ratio (LMR) are associated with poor prognostics in some cancers. Methods: This study is cross-sectional retrospective analytics that was conducted at Sanglah Hospital from June to August 2018. The research subject was medical records of intramedullary conventional osteosarcoma patients which fulfil inclusion and exclusion criteria. In this study, LMR as independent variable and Huvos score as dependent variable. Results: The result in this study showed positive correlation between LMR before neoadjuvan Chemotherapy and Huvos score (r=0.500) with p<0.05. Conclusions: A positive correlation was found between LMR and Huvos scores. Low LMR before neoadjuvan chemotheraphy (<2.81) were correlated with low huvos scores (grade I and II).